2005
DOI: 10.1111/j.1460-9568.2005.04138.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of organotypic ventral mesencephalic cultures from embryonic mice and protection against MPP+ toxicity by GDNF

Abstract: We characterized organotypic ventral mesencephalic (VM) cultures derived from embryonic day 12 (E12) mice (CBL57/bL6) in terms of number of dopaminergic neurons, cell soma size and dopamine production in relation to time in vitro and tested the effects of 1-methyl-4-phenylpyridinium (MPP(+)) and glial derived neurotrophic factor (GDNF) to validate this novel culture model. Dopamine production and dopaminergic neuron soma size increased dramatically with time in vitro, whereas the number of dopamine neurons dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…It is well documented though that cell death is an early event, which should be bypassed in both the cultures and grafting experiments at the time of evaluation (Barker et al, 1996;Branton and Clarke, 1999;Clarkson et al, 1995;Mahalik et al, 1994). Thus, GDNF may have a greater effect on neurite formation than on cell viability of TH-positive neurons, a hypothesis also supported by others (Jacobsen et al, 2005).…”
Section: Discussionmentioning
confidence: 73%
“…It is well documented though that cell death is an early event, which should be bypassed in both the cultures and grafting experiments at the time of evaluation (Barker et al, 1996;Branton and Clarke, 1999;Clarkson et al, 1995;Mahalik et al, 1994). Thus, GDNF may have a greater effect on neurite formation than on cell viability of TH-positive neurons, a hypothesis also supported by others (Jacobsen et al, 2005).…”
Section: Discussionmentioning
confidence: 73%
“…Organotypic mesencephalon cultures of embryonic day 12 (E12) mice were prepared as described previously (Jakobsen et al. , 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, delineating molecular mechanisms that regulate survival of the SNC dopaminergic neurons may provide an avenue for better treatment or prevention of PD. To this end, numerous studies in vitro, in animal models that recapitulate PD, and in human PD patients, have shown that glial cell-line derived neurotrophic factor (GDNF) family ligands (GFLs) promote increased survival of SNC dopaminergic neurons, reduce functional deficits caused by dopaminergic toxins, and improve parkinsonian symptoms (Gash et al, 1996;Cheng et al, 1998;Date et al, 1998;Horger et al, 1998;Kordower et al, 2000;Tomac et al, 2000;Sun et al, 2004;Jakobsen et al, 2005). GFL ligands (GDNF and Neurturin) have been, or are in clinical trials in the treatment of PD (Gill et al, 2003;Slevin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%